DISCOURSE STRUCTURE OF LECTURE IN L2 IN THE INDONESIAN TERTIARY CONTEXT - Akhyar Rido; Fatimah Mulya Sari; Ria Augie Mayang Suri; Hady Duantoro (Proceedings of ISELT FBS Universitas Negeri Padang, 2017)
Discourse structure is an important issue in academic spoken discourse in L2 settings. An inability to recognize discourse structure is seen as one of main problems in understanding lecture in L2 as it aids to comprehension. It is therefore imperative to examine how lecturers are helping their students to cope with the lecture and become critical thinking individuals. This study aims at discovering the macro-discourse structure of literature lectures conducted in English in the Indonesian tertiary context. This study was conducted in a private higher learning institution in Lampung province, Indonesia and involved 2 selected literature lecturers. Usinga qualitative research design, observations and video-recordings of prose and drama lectures were carried out for a total of 4 sessions and 8 teaching hours. The findings demonstrate that all lectures were delivered in three phases namely introductory, main, and end parts. The specific episodes used were topic introduction, review, concept introduction and development, discussion, and summarization. Negotiation of meaning also took place during the lectures; in addition, highly interactive lectures were emphasized as both lecturers and students exchanged a large series of open and follow-up questions which indicated that lectures explored critical and logical thinking skills of the students. The results of this study can be used as a platform for lecturers and teachers to organize their literature lecture in a well-structured and an optimally effective way.